1988
DOI: 10.1017/s0317167100027475
|View full text |Cite
|
Sign up to set email alerts
|

Hypomelanosis of Ito. Neurological Complications in 34 Cases

Abstract: ABSTRACT:We studied 34 Spanish children with hypomelanosis of Ito. This disease has an incidence of 1 per 1000 new patients consulting a paediatric neurological service, or 1 per 8000-10,000 unselected patients in a children's hospital. About 94% of our patients show noncutaneous abnormalities. Mental retardation (IQ below 70) was present in 64.7%; another 14.7% had an IQ between 70 and 90, usually associated with poor school performance. Four children exhibited autistic behaviour. Seizures of various types we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 29 publications
(24 reference statements)
7
39
0
Order By: Relevance
“…16 Binocular heterochromia may arise as an isolated congenital anomaly or as an autosomal dominant trait. 16 Heterochromia iridum has also been reported in association with Sturge-Weber syndrome, 19 hypomelanosis of Ito, 20 and linear scleroderma. 21 Recently, Quinlan and Shwayder 22 reported a case of a large facial café au lait macule in association with heterochromia iridum.…”
Section: Congenital Anomalies and Abnormalities Of Iris Pigmentationmentioning
confidence: 98%
“…16 Binocular heterochromia may arise as an isolated congenital anomaly or as an autosomal dominant trait. 16 Heterochromia iridum has also been reported in association with Sturge-Weber syndrome, 19 hypomelanosis of Ito, 20 and linear scleroderma. 21 Recently, Quinlan and Shwayder 22 reported a case of a large facial café au lait macule in association with heterochromia iridum.…”
Section: Congenital Anomalies and Abnormalities Of Iris Pigmentationmentioning
confidence: 98%
“…RuizMaldonado et al [1992] reported a frequency of 1 in every 7,805 general pediatric outpatients, 1 in every 790 general pediatric dermatology outpatients, 1 in every 2,983 general pediatric inpatients, and 1 in every 63 pediatric dermatology inpatients. A frequency of 1 in every 8,000 to 10,000 patients of a general pediatric hospital and 1 in every 1,000 patients in a pediatric neurology service had been determined in Spain [Pascual-Castroviejo et al, 1988].…”
Section: Frequencymentioning
confidence: 99%
“…In the changes that occur far more frequently than in the normal popula tion, such as strabismus [5,8,9,11,[13][14][15], and palpebral anomalies [8,9,11,[13][14][15][16], an in terrelationship with HI seems likely. Also in those ocular anomalies that are characterized by impaired pigmentation, such as iris dyspigmentations [5,8,9,13,17] and tapetoretinal dyspigmentations [14], already described as tesselated and 'salt and pepper' fundus [8,9,11,13], a connection seems feasible. This is all the more likely, because the mother had lid anomalies with subsequent strabismus and mother and daughter had iris dyspigmenta tions in a similar pattern as well as tapetoreti nal dyspigmentations.…”
Section: Discussionmentioning
confidence: 99%
“…Although both patients had a tortuositas vasorum, no HI relatedness can be verified. In ta ble 1, ocular changes in both mother and daughter have been compared with all previ ously described changes [6,12,[17][18][19]. Changes other than those found in the eyes have all been described before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation